-5(t-1)+9t=7t-6

Simple and best practice solution for -5(t-1)+9t=7t-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(t-1)+9t=7t-6 equation:


Simplifying
-5(t + -1) + 9t = 7t + -6

Reorder the terms:
-5(-1 + t) + 9t = 7t + -6
(-1 * -5 + t * -5) + 9t = 7t + -6
(5 + -5t) + 9t = 7t + -6

Combine like terms: -5t + 9t = 4t
5 + 4t = 7t + -6

Reorder the terms:
5 + 4t = -6 + 7t

Solving
5 + 4t = -6 + 7t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-7t' to each side of the equation.
5 + 4t + -7t = -6 + 7t + -7t

Combine like terms: 4t + -7t = -3t
5 + -3t = -6 + 7t + -7t

Combine like terms: 7t + -7t = 0
5 + -3t = -6 + 0
5 + -3t = -6

Add '-5' to each side of the equation.
5 + -5 + -3t = -6 + -5

Combine like terms: 5 + -5 = 0
0 + -3t = -6 + -5
-3t = -6 + -5

Combine like terms: -6 + -5 = -11
-3t = -11

Divide each side by '-3'.
t = 3.666666667

Simplifying
t = 3.666666667

See similar equations:

| 83=x+59 | | 63-n=15 | | 7+5b=37 | | 42-5=x | | 6+3+c=19 | | (5x-6)+(2x+5)=180 | | 17-x=16-5 | | 37-12=c-5 | | 6+2+n=19 | | 56=x-7 | | -.3y+.1=.5 | | 50-t^2=0 | | 3x+6y=39 | | 9z-z=-1+6z-3-2 | | h=-16t^2+144 | | 5-2x=3x-1 | | 11y+2=10y-4 | | 2x-7=-7+5x | | -3+2x=-6x-91 | | 3x+7=6x-20 | | -7x-10=90+3x | | 2x+7=31+4x | | 4x-7=92-5x | | 3x+1=-11+6x | | 2+6x=7x-3 | | 6x+7=7+2x | | 4+3x=-3x+16 | | 4-7x=5x+148 | | (3+6g)12= | | 3x-9=7x-9 | | y=x^2+10x+16 | | 12+12y=10y-12 |

Equations solver categories